2015
DOI: 10.1111/hdi.12347
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of vitamin D supplementation on glycemic control in type 2 diabetic prevalent hemodialysis patients

Abstract: Vitamin D is claimed to have an adjuvant effect on glycemic control by dual action on pancreatic β-cells and insulin resistance. The aim of this study was to assess the possible effect of short-term alfacalcidol supply on glycemic control in type 2 diabetic hemodialysis (HD) patients. Twenty type 2 diabetic HD patients (using diet and oral drugs but not insulin) were randomly selected from our dialysis unit as well as 20 non-diabetic HD patients as control. A third group of 12 healthy subjects were studied as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is estimated that 1 billion people worldwide are vitamin D (Vit D) insufficient or deficient [8]. Vit D insufficiency has been linked to numerous pathological conditions including immune/autoimmune disorders and diabetes [9][10][11][12]. Vit D supplementation may diminish the prevalence and adverse outcomes of these diseases and may reduce all-cause mortality [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 1 billion people worldwide are vitamin D (Vit D) insufficient or deficient [8]. Vit D insufficiency has been linked to numerous pathological conditions including immune/autoimmune disorders and diabetes [9][10][11][12]. Vit D supplementation may diminish the prevalence and adverse outcomes of these diseases and may reduce all-cause mortality [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the results of the present study, Ibrahim et al . (2015)[ 28 ] showed that the taking vitamin D supplements for 6 months led to a significant increase in calcium level. One of the reasons for the difference between the results of this study and our results could be due to the differences in the statistical population.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Furthermore, recent studies suggest that vitamin D supplementation has beneficial effects on glucose homeostasis and glycemic control. [23,24] However, there are limited data on what the optimum vitamin D level might be, and still no consensus on the dose of vitamin D that should be administered to achieve a 25(OH) D concentration of 20 or 30 ng/mL. Different cutoff values for vitamin D have been suggested in literature.…”
Section: Discussionmentioning
confidence: 99%